Strategies for optimizing compliance of paediatric patients for seasonal antibacterial vaccination with sublingually administered PMBL - Rosaschino, F.; Cattaneo, L. (Acta Biomedica Atenei Parmensis, 2004)
The objective of this pilot study was to evaluate efficacy, tolerance and compliance of paediatric patients vis-à-vis a cycle of PMBL treatment (a sublingual tablet taken for ten consecutive days over three consecutive months). The study enrolled 89 children (65 randomised to the treated group and 24 to the control group). The study protocol included an enrolment check-up (T0) and follow-ups at two months (T1), three months (T2) and nine months (T3) following the end of treatment, during which episodes of RRI were recorded; the main blood chemistry, immunology and phlogosis parameters were measured, together with hepatic, renal and bone marrow toxicity indexes. The administration of PMBL led to a significant decrease in RRI in the treated group, not only among the same children in relation to the previous winter, but also in comparison with untreated children during the same winter (mean number of infective episodes per patient 7.84 vs. 4.78, p